Immune-Related Prognostic Model in Colon Cancer: A Gene Expression-Based Study - Yang, Haojie; Jin, Wei; Liu, Hua; Gan, Dan; Cui, Can; Han, Changpeng; Wang, Zhenyi (Frontiers in Genetics, 2020)
Mounting evidence supports that the malignant phenotypes of cancers are defined not only by the intrinsic activity of tumor cells but also by immune cells that are recruited and activated in tumor-related microenvironment. Here, we developed a diagnostic and prognostic model for colon cancer, based on expression profiles of immune-related genes and immune cell component. As a result, we found that B cell infiltration ratio, CD4+ T cells, as well as immune-related genes of TRIB3, CHGA, CASP7, LGALS4, LEP, NOX4, IL17A, and HSPD1 may be highly relevant with clinical outcome of colon cancer.